Optimum iterative water-filling algorithm for cognitive MIMO MAC - Fei WEI; Zhen YANG (Tongxin xuebao)
The sum-rate maximization problem of the cognitive multiple-input multiple-output multiple access channel (MIMO MAC) under transmit power and interference temperature constraints was addressed.By exploiting the partial dual decomposition technique to relax the interference temperature constraint,the original problem was decomposed into more tractable subproblems.An iterative algorithm,in which the dual variable update and the iterative water-filling computation were performed alternately,was proposed to obtain the optimum transmit covariance matrices that achieved the maximum sum-rate.Finally,simulation results have been presented to verify the effectiveness of the algorithm.